POLITIK HUKUM KETENTUAN PASAL 27 AYAT (3) UNDANG-UNDANG NOMOR 19 TAHUN 2016 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK DIKAITKAN DENGAN KEBEBASAN BERPENDAPAT (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The development of information technology today is inseparable from the era of globalization, one form of this technological progress can be seen from the increasing number of trade transactions using online media via the internet. In addition, through the internet, a person can communicate without being limited by time and space so that it can be said that the internet is one of the channels for people to express their opinions. However, it is unfortunate that the current technological developments are not accompanied by a good mentality, it can be seen from the many cases of defamation that have resulted in convictions. Starting from the problem of mutual ridicule, criticism that is considered insulting, or the spread of false information in the community (hoax). In such conditions it is deemed necessary to give birth to the ITE Law, the birth of the ITE Law also creates a polemic with the emergence of Article 27 Paragraph (3) which is considered by many as a rubber article with the intention of silencing the freedom of expression and opinion guaranteed in the constitution.This type of research the writer uses is normative legal research. Normative legal research is doctrinal legal research, also known as library research or documentary study which focuses on secondary data. The data collection technique in this research is literature study, in which the author takes quotes from books, literature, or supporting books related to the problems to be studied. In writing this thesis, the author uses descriptive analysis (descriptive analysis) which aims to provide a description of the research subject based on data obtained from the subject under study.The results of this thesis research conclude that Article 27 paragraph (3) of the ITE Law was entered suddenly at the last minute of the ratification of the ITE Bill into Law without any prior basis for consideration. regarding the need to formulate provisions regarding defamation and / or defamation where the main objective of the ITE Law is to regulate online trade (e-commerce) and electronic signatures (electronic signatures). The two freedom of opinion with social media after the enactment of the ITE Law has the potential to paralyze the people's right to express their aspirations in terms of expressing opinions, criticizing and complaining even though these are human rights protected by the state.Keywords: Political Law - Freedom of Opinion - ITE Law